Goal Attainment Scaling in rehabilitation: An educational review providing a comprehensive didactical tool box for implementing Goal Attainment Scaling - Rachel Bard-Pondarré; Claire Villepinte; Fabienne Roumenoff; Hélène Lebrault; Céline Bonnyaud; Charles Pradeau; Djamel Bensmail; Marie-Eve; Agata Krasny-Pacini (Medical Journals Sweden, 2023)
Context: Goal Attainment Scaling (GAS) is a person-centered and collaborative approach, allowing to assess the effectiveness of an intervention on personally relevant goals. However, GAS is not a "scale" but a heterogeneous group of methodologies, including many variations and lack of consensus on high quality GAS. Objective: The aim of this communication is to: 1. provide updated didactical information on GAS use in PRM practice and research; 2. increase awareness of GAS methodological challenges; 3. guide use of GAS as an integrated process of rehabilitation after goal setting and; 4. provide updated resources for self-directed learning and extensive supplemental material to increase knowledge and practical skills in GAS use. Methods: Educational literature review about current GAS applications relevant to PRM fields. Results: Practical advice is provided regarding clinical challenges in GAS: definition of 0 level, time-frame and means employed to attain the goal, dealing with unforeseen pattern of improvement, synthesizing the numerous significations of "SMART" goal acronym to guide best use of GAS, and thinking flexibility on the type of relevant goals that can be set. Challenges with GAS in rehabilitation research are presented in order to promote researcher's and reviewer's awareness on reliable use of GAS and encouraging best-use of GAS. LAY ABSTRACT The goal attainment scaling methodology is a relevant way of measuring the effectiveness of a treatment, by creating scales to measure whether the goals previously identified with the person have been achieved through the treatment. There are many goal attainment scaling methodological variants, with a significant impact on results, of which users are not always aware. The aims of this review of the literature regarding current applications of goal attainment scaling in Physical and Rehabilitation Medicine fields, are to  (i) provide up-to-date didactic information on the use of goal attainment scaling in Physical and Rehabilitation Medicine practice and research; (ii) raise awareness of the methodological challenges of goal attainment scaling; (iii) guide the use of goal attainment scaling to support the rehabilitation process after goal setting; and (iv) provide up-to-date resources for self-directed training. Practical guidelines are provided for the use of goal attainment scaling in clinical practice, and the challenges of use of this methodology in rehabilitation research are presented in order to educate researchers and evaluators on the reliable use of goal attainment scaling.